The Game “Quiz Besemah” Sebagai Media Untuk Memperkenalkan Budaya Kota Pagar Alam - Lendy Rahmadi; Medi Triawan (Journal of Information System and Informatics, 2021)
Pagar Alam City has great potential in the field of tourism, both natural and cultural tourism. Pagar Alam City is also known as one of the Besemah tribal areas with various cultural heritages. Game "Quiz Besemah" is a mobile quiz and educational game specially designed for learning the culture and traditions of the city of Pagar Alam. The development method used in this research is Game Development Life Cycle (GDLC) with six stages, namely Initiation Developer, Pre-Production, Production, Testing, Beta External Testing and Release Game. The game engine for developing game features will use the Unity application so that it can support various platforms such as web, windows, mac, android, iOS, Xbox, Playstation 3 and Wii. The game that was built consisted of 20 (twenty) questions randomly and divided into 4 (four) classifications, namely basic, easy, medium and difficult. This game is recommended and user friendly for children aged 8-13 years. Based on the results of testing the application that has been built, it can be concluded that the game can be used as a learning medium for the introduction of Besemah culture in Pagar Alam City